Metal lithium negative electrode current collector and preparation method thereof, metal lithium negative electrode and preparation method thereof, and metal lithium battery

By using a carbon nanocage with a hollow chamber and a graphitized carbon layer shell in the metal lithium anode and covering it with a protective layer containing lithium compounds thereon, the metal lithium anode current collector is solved, and the metal lithium anode has poor volume expansion, dendrite growth and circulation performance during charging and discharge, achieving better circulation performance and safety.

CN116072881BActive Publication Date: 2025-04-01CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111294720.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-03
Publication Date
2025-04-01
Estimated Expiration
2041-11-03

AI Technical Summary

Technical Problem

During the charging and discharging process, metal lithium negative electrodes are prone to infinite volume expansion, poor dendrites' growth and circulation performance, resulting in increased safety hazards and commercial application difficulties.

Method used

A carbon nanocage with a hollow chamber and a graphitized carbon layer shell is used as the substrate, and a protective layer containing lithium compounds is conformally covered on its graphitized carbon layer shell to form a metal lithium negative electrode current collector. The current collector reacts in contact with the lithium salt pretreatment liquid to form an environment where metal lithium is uniformly grown in the carbon nanocage, inhibiting dendrites' growth and volume expansion.

Benefits of technology

It effectively inhibits the growth and volume expansion of metal lithium dendrites, improves the circulation performance of metal lithium negative electrodes, and promotes its commercial application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116072881B_ABST
    Figure CN116072881B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of metal lithium negative electrodes, and discloses a metal lithium negative electrode current collector and a preparation method thereof, a metal lithium negative electrode and a preparation method thereof, and a metal lithium battery. The current collector comprises a substrate and a protective layer, wherein the substrate is a carbon nano cage having a hollow chamber and a graphitized carbon layer shell; the protective layer conformally covers the outer surface and / or the inner surface of the graphitized carbon layer shell; the protective layer contains a lithium-containing compound, wherein the lithium-containing compound is selected from at least one of LiF, Li2CO3, LiOH, Li3PO4, LiPF6, LiTFSI, LiFSI, Li2SO3, LiNO3, Li2O, Li3N and R1-COOLi, and R1 is C1-C 20 The hollow chamber of the current collector provides a site for the storage of metallic lithium, and the graphitized carbon layer shell makes it have good mechanical strength and high lithium ion conductivity; the lithium-containing compound in the protective layer promotes more uniform deposition of metallic lithium, further inhibits the growth of metallic lithium dendrites, reduces volume changes, and improves the cycle performance of the metallic lithium negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of metal lithium negative electrodes, and in particular to a metal lithium negative electrode current collector and a preparation method thereof, a metal lithium negative electrode and a preparation method thereof, and a metal lithium battery. Background Art

[0002] With the booming development of electronic products and the progress of automobile electrification, society's demand for the specific energy of battery energy storage devices is increasing. The energy density of traditional lithium-ion batteries has reached a bottleneck (260Wh·kg -1 ), it is difficult to meet the needs. In recent years, due to the high theoretical specific capacity of lithium metal (3860mAh g -1 ) and low electrode potential (-3.04V vs SHE (standard hydrogen electrode)), the metal lithium negative electrode has received extensive attention from battery researchers. However, the application of metal lithium as a negative electrode for batteries still faces many problems. Since metal lithium has high reactivity and is easy to react with organic electrolytes, these reactions will lead to reduced utilization of metal lithium and electrolytes, and will be accompanied by a large amount of gas generation, which can easily cause safety hazards of metal lithium batteries. Secondly, after multiple charge and discharge of the battery, lithium dendrites will continue to grow on the surface of metal lithium. A large number of dendrites have a large stress on the diaphragm, causing the diaphragm to be pierced, thereby causing thermal runaway problems such as battery short circuit, fire, gas production and explosion. In addition, the unlimited volume expansion of metal lithium will also lead to various problems such as lithium electrode pulverization, electrolyte consumption, and large-scale gas production. These problems make it difficult for metal lithium negative electrodes to be commercially applied.

[0003] In order to solve these problems, there are three types of methods, each of which has certain limitations. The first type is to modify the electrolyte. Adding additives to the electrolyte helps to generate a stable SEI film, but a specific electrolyte can only be applied to a specific positive / negative electrode, with a narrow scope of application and high cost; the second type is to modify the surface of the metal lithium negative electrode to form a dense and strong passivation layer on the surface of the lithium negative electrode. The specific lithium negative electrode obtained by this method is also narrowly applicable and can only be applied to the battery system of the corresponding electrolyte and positive electrode. At the same time, surface modification will inevitably cause problems such as cumbersome process and high cost. The third type is to use a three-dimensional nanomaterial with a certain strength and stable structure as a current collector to form a composite negative electrode with metal lithium. Commonly used three-dimensional materials include metal foam, polymer fiber mesh and carbon nanonetwork. Metal foam materials have good structural strength, stability, conductivity, and wettability with lithium, but the density is high, which damages the overall specific capacity performance of the composite electrode. In addition, the active skeleton will inevitably lead to side reactions. Although the polymer fiber mesh has good structural strength and stability, it has poor conductivity and wettability with metal lithium. Carbon materials have good electrical conductivity and low density, but the carbon nanonetworks that are widely studied currently have metallic lithium deposited on the surface, leaving lithium exposed and prone to side reactions with the electrolyte. Hollow carbon cages have high electrical conductivity, good chemical stability, and a porous structure, which can solve many key problems in electrochemical storage, including severe agglomeration of active materials, slow electron and ion transport, volume expansion of active materials, poor interface stability, and cycle stability. Therefore, hollow carbon cages have been widely regarded as an effective conduction network for lithium ions and electrons, an elastic buffer that adapts to material volume changes, and an ideal and sturdy scaffold for metallic lithium anodes.

[0004] However, there are still many difficulties to be overcome in the practical application of hollow carbon cages as metal lithium negative electrode current collectors, such as large particle size, low degree of graphitization, harsh preparation conditions, complex process, poor compatibility with existing battery systems, poor operability and a series of problems. CN110875471A discloses a metal lithium @ carbon composite material, which includes hollow carbon particles with a closed filling chamber. The hollow carbon particles have large particle size, low curvature, long ion transmission distance, poor electrolyte wettability, and uneven current distribution, which hinders lithium ions from entering the hollow carbon cage for deposition; low degree of graphitization, poor mechanical properties, and low lithium ion conductivity, which are not effective in practical applications. In addition, the use of hollow carbon cages as hosts for lithium deposition, due to the diversity of pore structures, cannot completely ensure that the electrolyte can enter the hollow cage during the battery cycle, resulting in the inability of metal lithium to be deposited inside the cage, and poor cycle performance. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of unlimited volume expansion of metal lithium negative electrode, growth of metal lithium dendrites and poor cycle performance in the prior art, and to provide a metal lithium negative electrode current collector and a preparation method thereof, a metal lithium negative electrode and a preparation method thereof and a metal lithium battery to inhibit the growth of metal lithium dendrites and the volume expansion of the metal lithium negative electrode and improve the cycle performance of the metal lithium negative electrode.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a metal lithium negative electrode current collector, the current collector comprises a substrate and a protective layer, the substrate is a carbon nano cage having a hollow cavity and a graphitized carbon layer shell; the protective layer conformally covers the outer surface and / or the inner surface of the graphitized carbon layer shell; the protective layer contains a lithium-containing compound, the lithium-containing compound is selected from LiF, Li 2 CO 3 、LiOH、Li 3 PO 4 、LiPF 6 、LiTFSI、LiFSI、Li 2 SO 3 、LiNO 3 , Li 2 O. Li 3 N and R 1 -At least one of COOLi, R 1 C 1 -C 20 alkyl.

[0007] A second aspect of the present invention provides a method for preparing a metallic lithium negative electrode current collector, the method comprising:

[0008] The substrate is contacted with a pretreatment liquid for reaction; the substrate is a carbon nano cage having a hollow cavity and a graphitized carbon layer shell; the pretreatment liquid contains a lithium salt, and the lithium salt is selected from LiPF 6 , LiTFSI, LiFSI and LiNO 3 At least one of .

[0009] The third aspect of the present invention provides a metallic lithium negative electrode, which comprises a metal foil and an active layer composited on the metal foil, wherein the active layer comprises a binder, an optional conductive agent, a current collector and metallic lithium filled inside the current collector, and the current collector is the metallic lithium negative electrode current collector described in the first aspect or is the metallic lithium negative electrode current collector prepared according to the method described in the second aspect.

[0010] A fourth aspect of the present invention provides a method for preparing a metallic lithium negative electrode, the method comprising:

[0011] The slurry containing the current collector, the binder, and the optional conductive agent and solvent is coated on the metal foil, dried, rolled or not rolled, and then subjected to an electrodeposition reaction with metallic lithium;

[0012] The current collector is the metal lithium negative electrode current collector described in the first aspect or the metal lithium negative electrode current collector prepared according to the method described in the second aspect.

[0013] The fifth aspect of the present invention provides a metal lithium battery, which includes a pole core and a non-aqueous electrolyte, wherein the pole core and the non-aqueous electrolyte are sealed in a battery casing, the pole core includes a positive electrode, a negative electrode and a diaphragm, and the diaphragm is located between the positive electrode and the negative electrode, characterized in that the negative electrode is the metal lithium negative electrode described in the third aspect or is a metal lithium negative electrode prepared according to the method described in the fourth aspect.

[0014] Through the above technical solution, the present invention has the following advantages:

[0015] The metal lithium negative electrode current collector provided by the present invention has a small particle size and a large curvature, which is conducive to inducing metal lithium to enter the hollow cavity of the matrix (carbon nanocage) for deposition; the huge internal cavity of the hollow carbon nanocage provides a site for metal lithium storage, and preferably the matrix (carbon nanocage) also has a porous structure, which can also be used to accommodate metal lithium, thereby effectively inhibiting the growth of metal lithium dendrites and reducing the change in the volume of the metal lithium negative electrode. At the same time, the graphitized carbon layer shell of the matrix (carbon nanocage) can make the metal lithium negative electrode current collector have better mechanical strength, high lithium ion conductivity and is conducive to the formation of high-quality SEI; in addition, it can also avoid direct contact between metal lithium and electrolyte, and avoid the occurrence of side reactions; furthermore, in the metal lithium negative electrode current collector, the lithium-containing compound contained in the protective layer conformally covering the outer surface and / or inner surface of the graphitized carbon layer shell can promote the uniform growth of metal lithium in the hollow cavity of the carbon nanocage, further inhibit the growth of metal lithium dendrites and reduce the volume change, which is beneficial to improve the cycle performance of the metal lithium negative electrode and promote the commercial application of the metal lithium negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is an XPS graph of the metallic lithium negative electrode current collector prepared in Preparation Example 1;

[0017] Figure 2 It is a cycle performance diagram of the metal lithium negative electrode prepared in Examples 1, 2 and Comparative Example 1. DETAILED DESCRIPTION

[0018] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0019] The first aspect of the present invention provides a metal lithium negative electrode current collector, the current collector comprising a substrate and a protective layer, the substrate being a carbon nano cage having a hollow cavity and a graphitized carbon layer shell; the protective layer conformally covers the outer surface and / or the inner surface of the graphitized carbon layer shell; the protective layer contains a lithium-containing compound, the lithium-containing compound is selected from LiF, Li 2 CO 3 、LiOH、Li 3 PO 4 、LiPF 6 、LiTFSI、LiFSI、Li 2 SO 3 、LiNO 3 , Li 2 O. Li 3 N and R 1 -At least one of COOLi, R 1 C 1 -C 20 alkyl.

[0020] In the present invention, the term "hollow chamber" specifically refers to a porous hollow cage-shaped independent chamber surrounded by a graphitized carbon layer, wherein the graphitized carbon layer wraps around the outside of the chamber to form a graphitized carbon layer shell wrapping the hollow chamber.

[0021] According to some embodiments of the present invention, the hollow chamber provides a site for storing metallic lithium, which can effectively inhibit the growth of metallic lithium dendrites and reduce the volume change.

[0022] In the present invention, the term "graphitized carbon layer" refers to a carbon structure having a layered structure that can be clearly observed under a high-resolution transmission electron microscope, rather than an amorphous structure.

[0023] In the present invention, the term "conformal coverage" means that the protective layer covers the outer surface and / or inner surface of the outer shell of the graphitized carbon layer, but does not change the apparent morphology of the outer shell of the graphitized carbon layer.

[0024] According to some embodiments of the present invention, the protective layer may be continuous or discontinuous. Preferably, the protective layer is continuous.

[0025] The graphite-based hollow carbon cage particles in the prior art have large particle sizes (generally 200-800 nm), low curvature, and long ion transmission distances, which hinder the deposition of metallic lithium inside the hollow carbon cages, and have poor effects in practical applications.

[0026] According to some embodiments of the present invention, the diameter of the substrate is preferably 2-200 nm, preferably 10-50 nm, and more preferably 20-50 nm. The small diameter, large curvature, and short ion transmission distance of the substrate are conducive to the entry of metallic lithium into the hollow cavity of the substrate for deposition.

[0027] According to some embodiments of the present invention, preferably, the thickness of the outer shell of the graphitized carbon layer is 1-50 nm, preferably 1-10 nm, and more preferably 1-5 nm.

[0028] In the present invention, the surface morphology of the substrate is characterized by high-resolution transmission electron microscopy (HRTEM), the model of the high-resolution transmission electron microscope used is JEM-2100 (Japan Electron Co., Ltd.), and the high-resolution transmission electron microscope test conditions are: the acceleration voltage is 200kV. The diameter of the substrate and the thickness of the graphitized carbon layer shell can be measured through the high-resolution transmission electron microscope image.

[0029] According to some embodiments of the present invention, preferably, the volume of the hollow chamber accounts for 50-98% of the total volume, preferably 60-98%. The volume of the hollow chamber accounts for the total volume of the carbon nanocage within the above range, which can provide sufficient lithium deposition space and inhibit the growth of lithium dendrites.

[0030] According to some embodiments of the present invention, the protective layer contains a lithium-containing compound, and the lithium-containing compound is selected from LiF, Li 2 CO 3 、LiOH、Li 3 PO 4 、LiPF 6 、LiTFSI、LiFSI、Li 2 SO 3 、LiNO 3 , Li 2 O. Li 3 N and R 1 -At least one of COOLi, R 1 C 1 -C 20 The lithium-containing compound contained in the protective layer is conducive to promoting the uniform growth of metallic lithium inside the hollow cavity of the substrate, thereby effectively inhibiting the growth of metallic lithium dendrites and reducing the change in volume, thereby improving the cycle performance of the metallic lithium negative electrode.

[0031] According to some embodiments of the present invention, in order to further promote the uniform growth of metallic lithium in the hollow cavity of the substrate, further inhibit the growth of metallic lithium dendrites and reduce the volume change, preferably, the lithium-containing compound is selected from LiF, Li 2 CO 3 、LiOH、Li 2 O and Li 3 At least one of N.

[0032] According to some embodiments of the present invention, preferably, based on the total weight of the protective layer, the content of the lithium-containing compound in the protective layer is 100 wt %.

[0033] In the present invention, the content of the lithium-containing compound in the protective layer can be determined by X-ray photoelectron spectroscopy (XPS) analysis.

[0034] In the present invention, the X-ray photoelectron spectroscopy analysis was tested on an ESCALab250 X-ray photoelectron spectrometer equipped with ThermoAvantage V5.926 software from Thermo Scientific. The excitation source was monochromatic AlKα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis test was 6.53×10 -9 The electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.

[0035] According to some embodiments of the present invention, preferably, based on the total weight of the metal lithium negative electrode current collector, the content of the protective layer is 1-20% by weight, preferably 1-5% by weight.

[0036] According to some embodiments of the present invention, preferably, the specific surface area of ​​the substrate is 50-1000m 2 / g, preferably 200-600m 2 / g.

[0037] According to some embodiments of the present invention, preferably, the pore volume of the matrix is ​​1-2 cm 3 / g, preferably 1.5-1.8cm 3 / g.

[0038] According to some embodiments of the present invention, preferably, the pore size distribution curve of the matrix has at least one mesopore distribution peak. More preferably, the pore size distribution curve of the matrix has two mesopore distribution peaks; further preferably, in the pore size distribution curve of the matrix, there is a first mesopore distribution peak at 2-10 nm and a second mesopore distribution peak at 15-30 nm.

[0039] In the present invention, the term "mesopore" is defined as a pore with a pore size in the range of 2-50 nm.

[0040] In the present invention, the term "mesopore distribution peak" refers to a mesopore distribution peak on a pore distribution curve obtained by calculating a desorption curve according to the Barrett-Joyner-Halenda (BJH) method.

[0041] In the present invention, the pore structure properties of the material are detected by the BET test method. Specifically, the Quantachrome AS-6B analyzer is used for measurement, and the BET specific surface area and pore volume of the material are obtained by the Brunauer-Emmett-Taller (BET) method, and the mesopore distribution curve is obtained by calculating the desorption curve according to the Barrett-Joyner-Halenda (BJH) method.

[0042] According to some embodiments of the present invention, the matrix (carbon nanocage) may contain various doping elements that are known to those skilled in the art and can be applied to carbon materials, such as nitrogen, oxygen, sulfur, boron, phosphorus, fluorine, chlorine, bromine, iodine, etc. Preferably, the carbon nanocage does not contain nickel.

[0043] According to some embodiments of the present invention, preferably, in the Raman spectrum of the matrix, I D / I G The range is 0.2-1.2, preferably 0.2-0.5. The high graphitization degree of the matrix makes the metal lithium negative electrode current collector have better mechanical strength and higher lithium ion conductivity, and is conducive to the formation of high-quality SEI; in addition, it can also avoid direct contact between metal lithium and electrolyte and avoid the occurrence of side reactions.

[0044] In the present invention, the graphitization degree of the matrix is ​​characterized by Raman spectroscopy, 1355 cm -1 The peak (D peak) is attributed to structural defects and is amorphous carbon, 1585cm -1 The peak (G peak) is attributed to the carbon in the planar structure. Usually I D / I G (D peak and G peak intensity ratio) to characterize the degree of graphitization of the material. D / I GThe higher the value, the more defects there are and the lower the degree of graphitization. The Raman spectrum of the material is obtained using a RM2000 micro-confocal Raman spectrometer (product of Reinshaw Company), and the technical indicators are: the excitation source is a He-Ne laser with a wavelength of 525nm.

[0045] A second aspect of the present invention provides a method for preparing a metallic lithium negative electrode current collector, the method comprising:

[0046] The substrate is contacted with a pretreatment liquid for reaction; the substrate is a carbon nano cage having a hollow cavity and a graphitized carbon layer shell; the pretreatment liquid contains a lithium salt, and the lithium salt is selected from LiPF 6 , LiTFSI, LiFSI and LiNO 3 At least one of .

[0047] According to some embodiments of the present invention, in order to further improve the cycle performance of the metal lithium negative electrode, preferably, the substrate is contacted with the pretreatment solution for reaction at a pressure below 10 Pa.

[0048] According to some embodiments of the present invention, preferably, the usage ratio of the substrate to the pretreatment liquid is 0.1-0.3 g:15-25 mL, preferably 0.15-0.25 g:20-23 mL.

[0049] According to some embodiments of the present invention, preferably, the pretreatment liquid further contains a solvent; preferably, the solvent is an organic solvent, and more preferably, the solvent is selected from at least one of ethylene carbonate, dimethyl carbonate, 1,3-dioxolane and ethylene glycol dimethyl ether.

[0050] According to some embodiments of the present invention, there is no particular limitation on the preparation of the pretreatment solution. Preferably, the pretreatment solution is obtained by mixing a lithium salt with a solvent.

[0051] According to some embodiments of the present invention, preferably, in the pretreatment solution, the concentration of the lithium salt is 0.1-0.5 g / mL, preferably 0.15-0.3 g / mL.

[0052] According to some embodiments of the present invention, in the process of contacting and reacting the substrate with the pretreatment solution, due to the decomposition of the lithium salt and / or solvent contained in the pretreatment solution and the contact reaction with the substrate, a protective layer is formed on the outer surface and / or inner surface of the graphitized carbon layer shell in the prepared metal lithium negative electrode current collector, and the protective layer contains a lithium-containing compound, and the lithium-containing compound is selected from LiF, Li 2 CO 3 、LiOH、Li 3 PO 4 、LiPF 6 、LiTFSI、LiFSI、Li2 SO 3 、LiNO 3 , Li 2 O. Li 3 N and R 1 -At least one of COOLi, R 1 C 1 -C 20 Preferably, the lithium-containing compound is selected from LiF, Li 2 CO 3 、LiOH、Li 2 O and Li 3 At least one of N. The present invention has no particular limitation on the content of each species in the lithium-containing compound, and the content of each species in the lithium-containing compound can be determined according to conventional technical knowledge in the art.

[0053] According to some embodiments of the present invention, preferably, contacting the substrate with the pretreatment liquid for reaction comprises: dropping the pretreatment liquid onto the surface of the substrate and stirring.

[0054] According to some embodiments of the present invention, preferably, the contact reaction conditions include: temperature of 20-50°C, preferably 20-30°C; time of 1-10h, preferably 2-4h.

[0055] According to some embodiments of the present invention, preferably, the contact reaction is carried out under stirring conditions, and the stirring speed may be 200-1000 r / min.

[0056] According to some embodiments of the present invention, preferably, the method further comprises the step of drying the solid material obtained by the contact reaction. The present invention has no particular limitation on the drying conditions, as long as the excess pretreatment liquid on the surface of the solid material can be removed. The drying can be carried out under the condition of inert gas (preferably argon) circulation, the drying temperature is preferably 50-150°C, and the drying time is preferably 1-10h.

[0057] According to some embodiments of the present invention, there is no particular limitation on the source of the matrix, and a commercially available product may be used, or the matrix may be prepared by a method known in the art.

[0058] Preferably, the method for preparing the substrate comprises the following steps:

[0059] (1) providing a homogeneous solution containing a nickel source, an organic carboxylic acid and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor;

[0060] (2) calcining the precursor at a high temperature under an inert atmosphere or a reducing atmosphere to obtain a calcined product;

[0061] (3) contacting the calcined product with an acid for reaction, and then performing solid-liquid separation to obtain a matrix.

[0062] According to some embodiments of the present invention, the method for preparing the substrate is to prepare a precursor by reacting a nickel source and an organic carboxylic acid in a solvent, and then the precursor is subjected to high-temperature calcination and then acid washing, and the obtained substrate is a carbon nanocage having a hollow cavity and a graphitized carbon layer shell.

[0063] Preferably, the diameter of the matrix is ​​2-200 nm, preferably 10-50 nm, more preferably 20-50 nm.

[0064] Preferably, the volume of the hollow chamber accounts for 50-98% of the total volume of the carbon nanocage, preferably 60-98%.

[0065] Preferably, the thickness of the outer shell of the graphitized carbon layer is 1-50 nm, preferably 1-10 nm, and more preferably 1-5 nm.

[0066] Preferably, the specific surface area of ​​the substrate is 50-1000m 2 / g, preferably 200-600m 2 / g.

[0067] Preferably, the pore volume of the matrix is ​​1-2 cm 3 / g, preferably 1.5-1.8cm 3 / g.

[0068] Preferably, the pore size distribution curve of the matrix has at least one mesopore distribution peak, preferably two mesopore distribution peaks; more preferably, in the pore size distribution curve of the matrix, there is a first mesopore distribution peak at 2-10nm and a second mesopore distribution peak at 15-30nm.

[0069] Preferably, in the Raman spectrum of the matrix, I D / I G The range is 0.2-1.2, preferably 0.2-0.5.

[0070] According to some embodiments of the present invention, preferably, in step (1), the mass ratio of the nickel source to the organic carboxylic acid is 1:0.1-100, preferably 1:0.2-50, and more preferably 1:0.5-5.

[0071] According to some embodiments of the present invention, in step (1), the method for forming the homogeneous solution is not particularly limited by the present invention, for example, the homogeneous solution may be formed by heating, preferably by heating and stirring. The present invention also has no particular limitation on the heating temperature and stirring rate, as long as the homogeneous solution can be formed.

[0072] According to some embodiments of the present invention, preferably, the nickel source and the organic carboxylic acid are dissolved in a solvent to form a homogeneous solution. The present invention does not particularly limit the type of the solvent, and is subject to the ability to form a homogeneous solution. Preferably, the solvent is water and / or ethanol, more preferably water; the present invention does not particularly limit the amount of the solvent, and is also subject to the ability to form a homogeneous solution. The solvent in the homogeneous solution can be removed by direct evaporation, and the temperature and process of the evaporation can adopt the existing technology known to those skilled in the art. For example, the solvent in the homogeneous solution can be removed by heating and evaporating to dryness.

[0073] According to some embodiments of the present invention, preferably, the nickel source is selected from at least one of nickel acetate, nickel chloride, nickel carbonate and basic nickel carbonate, preferably basic nickel carbonate.

[0074] According to some embodiments of the present invention, preferably, the polybasic organic carboxylic acid is selected from at least one of citric acid, maleic acid, trimesic acid, terephthalic acid, malic acid, ethylenediaminetetraacetic acid and dipicolinic acid, preferably citric acid.

[0075] According to some embodiments of the present invention, preferably, in step (2), the conditions for high temperature calcination include: a heating rate of 0.5-30°C / min, preferably 1-10°C / min; a temperature of 600-1300°C, preferably 800-1100°C; and a time of 20-600min, preferably 60-480min. The high temperature calcination conditions within the above preferred range are conducive to improving the degree of graphitization of the carbon layer shell in the matrix.

[0076] According to some embodiments of the present invention, preferably, the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium; and / or

[0077] The reducing atmosphere is provided by hydrogen and optionally an inert gas, wherein the inert gas is at least one of nitrogen, argon, neon and helium.

[0078] According to some embodiments of the present invention, preferably, in step (3), the step of contacting the calcined product with an acid for reaction is: mixing the calcined product with an acid, and the present invention has no particular limitation on the mixing method, and the mixing can be carried out by ultrasound or stirring. The acid can be an acid conventionally used in the art, as long as it can form a carbon nanocage having a hollow cavity and a graphitized carbon layer shell.

[0079] According to some embodiments of the present invention, preferably, the acid is an inorganic acid and / or an organic acid, more preferably, the acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid, more preferably hydrochloric acid. More preferably, the acid is provided in the form of an aqueous solution; further preferably, in the aqueous solution of the acid, the concentration of the acid is 0.1-10 mol / L, preferably 1-3 mol / L.

[0080] According to some embodiments of the present invention, preferably, in step (3), the contact reaction conditions include: temperature of 20-110° C., preferably 60-90° C.; time of 0.1-48 h, preferably 4-12 h.

[0081] According to some embodiments of the present invention, in step (3), there is no particular limitation on the solid-liquid separation method, and it can be carried out by solid-liquid separation methods known in the art, for example, solid-liquid separation can be carried out by filtration, suction filtration, centrifugation, etc. The liquid obtained after solid-liquid separation can be reused as a raw material for preparing carbon nanocages.

[0082] According to some embodiments of the present invention, preferably, in step (3), the solid-liquid separation further includes washing and drying steps. The washing is used to remove the acid remaining on the carbon nano cage, and therefore, various water washing methods that can wash the carbon nano cage to neutrality are applicable to the present invention. The drying is used to remove water on the carbon nano cage. Drying can be carried out by normal pressure drying or reduced pressure drying, and the drying conditions can adopt any feasible existing technology, preferably, drying is carried out at 80-140°C.

[0083] According to some embodiments of the present invention, the metal lithium negative electrode current collector prepared by the method comprises a substrate and a protective layer, wherein the substrate is a carbon nanocage having a hollow cavity and a graphitized carbon layer shell; the protective layer conformally covers the outer surface and / or the inner surface of the graphitized carbon layer shell; the protective layer contains a lithium-containing compound, and the lithium-containing compound is selected from LiF, Li 2 CO 3 、LiOH、Li 3 PO 4 、LiPF 6 、LiTFSI、LiFSI、Li 2 SO 3 、LiNO 3 , Li 2 O. Li 3 N and R 1 -At least one of COOLi, R 1 C 1 -C 20 alkyl.

[0084] According to some embodiments of the present invention, the carbon nanocage may contain various doping elements known to those skilled in the art that can be applied to carbon materials, such as nitrogen, oxygen, sulfur, boron, phosphorus, fluorine, chlorine, bromine, iodine, etc. Preferably, the carbon nanocage does not contain nickel.

[0085] The third aspect of the present invention provides a metallic lithium negative electrode, which comprises a metal foil and an active layer composited on the metal foil, wherein the active layer comprises a binder, an optional conductive agent, a current collector and metallic lithium filled inside the current collector, and the current collector is the metallic lithium negative electrode current collector described in the first aspect or is the metallic lithium negative electrode current collector prepared according to the method described in the second aspect.

[0086] According to some embodiments of the present invention, there is no particular limitation on the composite method. For example, the active layer can be composited onto the metal foil by coating and / or calendering.

[0087] According to some embodiments of the present invention, preferably, metallic lithium is filled in the hollow cavity of the metallic lithium negative electrode current collector; and / or metallic lithium passes through the graphitized carbon layer shell and / or protective layer of the metallic lithium negative electrode current collector and is filled in the hollow cavity.

[0088] According to some embodiments of the present invention, preferably, in the metal lithium negative electrode, based on the total weight of the active layer, the content of metal lithium is 2-90% by weight, preferably 10-50% by weight. The content of metal lithium within the above preferred range is conducive to further improving the cycle performance of the metal lithium negative electrode.

[0089] According to some embodiments of the present invention, preferably, in the metal lithium negative electrode, based on the total weight of the active layer, the content of the metal lithium negative electrode current collector is 20-50% by weight, preferably 25-40% by weight. The content of the current collector within the above preferred range is conducive to further promoting the uniform deposition of metal lithium.

[0090] According to some embodiments of the present invention, preferably, in the metal lithium negative electrode, based on the total weight of the active layer, the content of the binder is 5-20% by weight, preferably 10-20% by weight.

[0091] According to some embodiments of the present invention, preferably, in the metal lithium negative electrode, based on the total weight of the active layer, the content of the conductive agent is 0-10 wt %. In order to increase the conductivity of the material, more preferably, the content of the conductive agent is 5-10 wt %.

[0092] According to some embodiments of the present invention, preferably, the thickness of the active layer is 5-50 μm, preferably 10-50 μm.

[0093] According to some embodiments of the present invention, preferably, the metal foil is selected from at least one of copper foil, titanium foil, nickel foil and alloy foils thereof, preferably copper foil. Preferably, the metal foil has a thickness of 5-20 μm, preferably 8-10 μm.

[0094] According to some embodiments of the present invention, the binder can be any binder known in the art that can be used for metal lithium batteries, for example, it can be selected from fluorine-containing resins and / or polyolefin compounds. Preferably, the binder is selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber emulsion and acrylonitrile copolymer aqueous dispersion, preferably polyvinylidene fluoride.

[0095] According to some embodiments of the present invention, the conductive agent may be various conductive agents known to those skilled in the art. Preferably, the conductive agent is selected from at least one of conductive carbon black (Super-P), acetylene black, nickel powder, copper powder and conductive graphite, preferably conductive carbon black.

[0096] According to some embodiments of the present invention, the metallic lithium negative electrode includes a metal foil and an active layer composited on the metal foil, the active layer contains a metallic lithium negative electrode current collector, the hollow chamber of the metallic lithium negative electrode current collector is filled with metallic lithium, and also has a protective layer conformally covering the outer surface and / or inner surface of the graphitized carbon layer shell, combined with a binder and an optional conductive agent, it not only has better mechanical strength and higher lithium ion conductivity, but also is conducive to the formation of high-quality SEI; in addition, it can also avoid direct contact between metallic lithium and electrolyte, avoid the occurrence of side reactions, and is conducive to improving the cycle performance of the metallic lithium negative electrode.

[0097] A fourth aspect of the present invention provides a method for preparing a metallic lithium negative electrode, the method comprising:

[0098] The slurry containing the current collector, the binder, and the optional conductive agent and solvent is coated on the metal foil, dried, rolled or not rolled, and then subjected to an electrodeposition reaction with metallic lithium;

[0099] The current collector is the metal lithium negative electrode current collector described in the first aspect or the metal lithium negative electrode current collector prepared according to the method described in the second aspect.

[0100] According to some embodiments of the present invention, the electrodeposition may be performed by an electrodeposition method known in the art, as long as the metal lithium can be filled in the hollow cavity of the metal lithium negative electrode current collector; and / or the metal lithium passes through the graphitized carbon layer shell and / or the protective layer of the metal lithium negative electrode current collector and is filled in the hollow cavity. Preferably, the electrodeposition is constant direct current electrodeposition and / or pulse electrodeposition, preferably constant direct current electrodeposition.

[0101] According to some embodiments of the present invention, the type and amount of the solvent are well known to those skilled in the art, and all solvents known in the art that can be used for the preparation of metal lithium battery electrodes can be used. Preferably, the solvent is anhydrous ethanol and / or N-methylpyrrolidone (NMP), preferably N-methylpyrrolidone.

[0102] According to some embodiments of the present invention, preferably, the mass ratio of the matrix, the binder and the conductive agent is 50-90:5-20:0-10, for example, it can be 9:0.5:0.5, 8:1:1, 8:0.5:1, 9:1:0 and any value in the range formed by any two of these values, preferably 60-80:10-20:5-10, and more preferably 8:1:1.

[0103] The fifth aspect of the present invention provides a metal lithium battery, which includes a pole core and a non-aqueous electrolyte, wherein the pole core and the non-aqueous electrolyte are sealed in a battery casing, the pole core includes a positive electrode, a negative electrode and a diaphragm, and the diaphragm is located between the positive electrode and the negative electrode, characterized in that the negative electrode is the metal lithium negative electrode described in the third aspect or is a metal lithium negative electrode prepared according to the method described in the fourth aspect.

[0104] According to some embodiments of the present invention, the non-aqueous electrolyte may be a non-aqueous electrolyte suitable for metal lithium batteries conventionally used in the art, preferably, the non-aqueous electrolyte is selected from an organic electrolyte, more preferably an ether electrolyte LiTFSI / DOL / DME. The injection volume of the electrolyte is generally 20-100 μL, and the concentration of the electrolyte is generally 0.2-8.0 mol / L.

[0105] According to some embodiments of the present invention, the diaphragm has electrical insulation performance and liquid retention performance, is disposed between the positive electrode and the negative electrode of the pole core, and is sealed in the battery housing together with the pole core. The diaphragm can be various diaphragms commonly used in the art, such as diaphragms of various production grades produced by various well-known manufacturers by personnel in the art. Preferably, the diaphragm is selected from any one of polyethylene film, polypropylene film, modified polyethylene felt, modified polypropylene felt, ultrafine glass fiber felt, vinylon felt or nylon felt and wettable polyolefin microporous membrane by welding or bonding. The diaphragm is more preferably a polypropylene film.

[0106] According to some embodiments of the present invention, the metal lithium battery can directly use sulfur, lithium iron phosphate, etc. as the positive electrode.

[0107] According to some embodiments of the present invention, preferably, the metal lithium battery is any one of a lithium oxygen battery, a lithium sulfur battery, a lithium selenium battery, a lithium tellurium battery, a lithium iodine battery, a lithium carbon dioxide battery and a lithium nitrogen battery.

[0108] The present invention will be described in detail below by way of examples. In the following examples and comparative examples:

[0109] The surface morphology of the material was characterized by high-resolution transmission electron microscopy (HRTEM). The model of the high-resolution transmission electron microscope used was JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope were: the acceleration voltage was 200 kV.

[0110] The pore structure properties of the material were detected by the BET test method. Specifically, the Quantachrome AS-6B analyzer was used for the determination. The specific surface area of ​​the material was obtained by the Brunauer-Emmett-Taller (BET) method, and the pore size distribution curve was calculated by the desorption curve according to the Barrett-Joyner-Halenda (BJH) method.

[0111] The composition and valence state changes of each element on the surface of the material were determined by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy analysis was carried out on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis was 6.5×10 -10 The electron binding energy was calibrated with the C1s peak (284.3 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.

[0112] The graphitization degree of the material was characterized by Raman spectroscopy, 1355 cm -1 The peak (D peak) is attributed to structural defects and is amorphous carbon, 1585cm -1 The peak (G peak) is attributed to the carbon in the planar structure. Usually I D / I G (D peak and G peak intensity ratio) to characterize the degree of graphitization of carbon materials. D / I G The higher the value, the more defects there are and the lower the degree of graphitization. The Raman spectrum of the material is obtained using a RM2000 micro-confocal Raman spectrometer (a product of Reinshaw). Technical indicators: The excitation source is a He-Ne laser with a wavelength of 532nm.

[0113] The carbon nanocage is prepared by the following method:

[0114] S1: Weigh 20 g of basic nickel carbonate and 20 g of citric acid, add them into a beaker containing 100 mL of deionized water, stir at 80° C. to obtain a homogeneous solution, and continue heating and evaporating to obtain a precursor.

[0115] S2: The obtained precursor is placed in a porcelain boat, and then the porcelain boat is placed in the constant temperature zone of a tube furnace, nitrogen is introduced at a flow rate of 80 mL / min, and the temperature is increased to 1100°C at a rate of 10°C / min. After keeping the constant temperature for 2 hours, the heating is stopped, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.

[0116] S3: The obtained pyrolysis product is added to an aqueous solution containing 1M hydrochloric acid and stirred at 90°C for 4 hours, then filtered, the filtrate is collected, and then washed with deionized water until the filtrate is neutral, and then the filter cake is dried in a constant temperature oven at 120°C for 6 hours to obtain a carbon nanocage.

[0117] Transmission electron microscopy showed that the carbon nanocage had a hollow cavity and a graphitized carbon layer shell, and the thickness of the graphitized carbon layer shell was 2 nm. The diameter of the carbon nanocage was 20 nm, and it had obvious graphite carbon lattice stripes.

[0118] The BET test method showed that the specific surface area of ​​the carbon nanocage was 467 m 2 / g, pore volume 1.797cm 3 / g; in the material, the volume of the hollow cavity accounts for 98% of the total volume of the carbon nanocage; in the BJH pore size distribution curve of the carbon nanocage, there are two mesopore distribution peaks at 3nm and 18nm.

[0119] Raman analysis showed that the carbon nanocage D / I G It is 0.4118, indicating that the carbon nanocage has a high degree of graphitization.

[0120] Preparation Examples 1-3 are used to illustrate the metal lithium negative electrode current collector and the preparation method thereof provided by the present invention.

[0121] Preparation Example 1

[0122] (1) 0.2 g of carbon nanocages were placed in a flask and vacuumed to below 10 Pa;

[0123] (2) 5.74 g of LiTFSI was dissolved in 20 mL of DOL / DME (volume ratio 1:1), and 1% of LiNO was added. 3, mixed to form a homogeneous solution to obtain a pretreatment solution (wherein the concentration of lithium salt is 0.3 g / mL), and then the pretreatment solution is quickly added dropwise to the flask, stirred at 25°C for 2 hours, and then the mixed liquid is filtered, and the filter cake is placed in a forced air drying oven and dried at 80°C for 12 hours to obtain a metallic lithium negative electrode current collector.

[0124] The XPS data of the metal lithium negative electrode current collector at different etching depths are as follows Figure 1 As shown in the figure, the outer surface and inner surface of the graphitized carbon layer shell of the metal lithium negative electrode current collector form an effective protective layer, and the lithium-containing compounds contained in the protective layer include LiF, Li 2 CO 3 、LiOH、Li 2 O and Li 3 N, based on the total weight of the protective layer, the content of the lithium-containing compound is 100 wt%. This indicates that the vacuum infiltration electrolyte method can ensure that there is enough electrolyte in the hollow cavity of the carbon nanocage of the metal lithium negative electrode current collector, which is conducive to forming an effective protective layer on the inner surface of the graphitized carbon layer shell, thereby further inhibiting the growth of lithium dendrites.

[0125] Based on the total weight of the metal lithium negative electrode current collector, the content of the protective layer is 5 weight %.

[0126] Preparation Example 2

[0127] The method of Preparation Example 1 is followed, except that in step (1), after the carbon nanocage is placed in the flask, the step of evacuating to below 10 Pa is not performed, and the remaining raw materials, steps and conditions are the same as those in Preparation Example 1 to obtain a metallic lithium negative electrode current collector.

[0128] XPS analysis shows that the metal lithium negative electrode current collector only forms a protective layer on the outer surface of the graphitized carbon layer shell, and the lithium-containing compounds contained in the protective layer include LiF, Li 2 CO 3 、LiOH、Li 2 O and Li 3 N, based on the total weight of the protective layer, the content of the lithium-containing compound is 100 wt%.

[0129] Based on the total weight of the metal lithium negative electrode current collector, the content of the protective layer is 4 weight %.

[0130] Preparation Example 3

[0131] (1) 0.2 g of carbon nanocages were placed in a flask and vacuumed to below 10 Pa;

[0132] (2) 3 g of LiPF 6Dissolve in 20 mL of EC / DEC (volume ratio 1:1), mix to form a homogeneous solution, and obtain a pretreatment solution (wherein the concentration of lithium salt is 0.15 g / mL). Rapidly add the pretreatment solution dropwise into the flask, stir at 25 °C for 2 h, filter the mixed liquid, and place the filter cake in a forced air drying oven at 80 °C for 12 h to obtain a metallic lithium negative electrode current collector.

[0133] XPS analysis shows that the outer surface and inner surface of the graphitized carbon layer shell of the metal lithium negative electrode current collector form an effective protective layer, and the lithium-containing compounds contained in the protective layer include LiF, Li 2 CO 3 , LiOH and Li 2 O, based on the total weight of the protective layer, the content of the lithium-containing compound is 100 wt%. This indicates that the vacuum infiltration electrolyte method can ensure that there is enough electrolyte in the hollow cavity of the carbon nanocage of the metal lithium negative electrode current collector, which is conducive to forming an effective protective layer on the inner surface of the graphitized carbon layer shell, thereby further inhibiting the growth of lithium dendrites.

[0134] Based on the total weight of the metal lithium negative electrode current collector, the content of the protective layer is 3 weight %.

[0135] Examples 1-3 are used to illustrate the metal lithium negative electrode and the preparation method thereof provided by the present invention.

[0136] Example 1

[0137] (1) The metal lithium negative electrode current collector obtained in Preparation Example 1, the conductive agent Super-P and the NMP solution of the binder PVDF were mixed (the mass ratio of the metal lithium negative electrode current collector, the conductive agent and the binder was 8:1:1). The specific method is: the dried metal lithium negative electrode current collector and the conductive agent were ground in a mortar for 15 minutes, and after grinding evenly, PVDF solution (mass fraction 5%) was added according to the proportion, and stirred on a magnetic stirrer for 6 hours; the obtained paste slurry was evenly coated on a copper foil with a thickness of 10 μm, and then dried in a vacuum drying oven at 60°C for 20 hours, and then made into a disc with a diameter of 12 mm, and maintained at a pressure of 8 MPa for 60 seconds to obtain a pole piece.

[0138] (2) The electrode was used as the working electrode, metallic lithium was used as the counter electrode, Celgard membrane was used as the diaphragm, 1 mol / L lithium bis(trifluoromethylsulfonyl)imide (CAS: 90076-65-6) was selected as the electrolyte, 1% lithium nitrate was used as the additive, and the solvent volume ratio DOL (1,3-dioxolane): DME (ethylene glycol dimethyl ether) = 1:1 was assembled into a CR2032 button cell.

[0139] (3) The battery was subjected to constant current metal lithium deposition using a LAND CT2001A charge and discharge instrument from Wuhan Rambo Electronics Co., Ltd., i.e., at a constant current of 1 mA cm -2 After discharging for 4 hours under the same conditions, the electrode sheet was taken out to obtain the metallic lithium negative electrode A1.

[0140] In the metal lithium negative electrode, based on the total weight of the active layer, the content of metal lithium is 50 weight%, the content of the metal lithium negative electrode collector is 30 weight%, the content of the binder PVDF is 10 weight%, and the content of the conductive agent Super-P is 10 weight%; the thickness of the active layer in the metal lithium negative electrode is 50 μm.

[0141] Example 2

[0142] A metal lithium negative electrode was prepared according to the method of Example 1, except that in step (1), the metal lithium negative electrode current collector obtained in Preparation Example 1 was replaced by the metal lithium negative electrode current collector obtained in Preparation Example 2 to obtain a metal lithium negative electrode A2.

[0143] In the metal lithium negative electrode, based on the total weight of the active layer, the content of metal lithium is 50 weight%, the content of the metal lithium negative electrode collector is 30 weight%, the content of the binder PVDF is 10 weight%, and the content of the conductive agent Super-P is 10 weight%; the thickness of the active layer in the metal lithium negative electrode is 50 μm.

[0144] Example 3

[0145] A metal lithium negative electrode was prepared according to the method of Example 1, except that in step (1), the metal lithium negative electrode current collector obtained in Preparation Example 1 was replaced by the metal lithium negative electrode current collector obtained in Preparation Example 3 to obtain a metal lithium negative electrode A3.

[0146] In the metal lithium negative electrode, based on the total weight of the active layer, the content of metal lithium is 50 weight%, the content of the metal lithium negative electrode collector is 30 weight%, the content of the binder PVDF is 10 weight%, and the content of the conductive agent Super-P is 10 weight%; the thickness of the active layer in the metal lithium negative electrode is 50 μm.

[0147] Comparative Example 1

[0148] A metal lithium negative electrode was prepared according to the method of Example 1, except that in step (1), the metal lithium negative electrode current collector obtained in Preparation Example 1 was replaced with a carbon nanocage to obtain a metal lithium negative electrode D1.

[0149] In the metal lithium negative electrode, based on the total weight of the active layer, the content of metal lithium is 50 weight%, the content of the metal lithium negative electrode collector is 30 weight%, the content of the binder PVDF is 10 weight%, and the content of the conductive agent Super-P is 10 weight%; the thickness of the active layer in the metal lithium negative electrode is 50 μm.

[0150] Test Case

[0151] (1) Battery assembly: The metal lithium negative electrodes A1-A3 prepared in Examples 1-3 were used as negative electrodes, metal lithium sheets were used as positive electrodes, Celgard membranes were used as separators, 1 mol / L lithium bis(trifluoromethylsulfonate)imide (CAS: 90076-65-6) was used as electrolyte, 1% lithium nitrate was used as additive, and the solvent volume ratio was DOL (1,3-dioxolane): DME (ethylene glycol dimethyl ether) = 1:1, and assembled into CR2032 button batteries.

[0152] (2) Charge and discharge test: The obtained batteries were subjected to constant current charge and discharge tests using a LAND CT2001A charge and discharge instrument from Wuhan Rambo Electronics Co., Ltd. -2 Under the conditions of charge and discharge for 1 hour each, and cycle, the cycle results are as follows Figure 2 As shown in the figure:

[0153] The metal lithium negative electrode A1 prepared in Example 1 has a 2 @1mAh / cm 2 The cycle life under the conditions is 450h.

[0154] The metal lithium negative electrode A2 prepared in Example 2 has a 2 @1mAh / cm 2 The cycle life under the conditions is 250h.

[0155] Comparative test example

[0156] The battery was assembled, charged and discharged, and the metal lithium negative electrode was disassembled and characterized according to the method of the test example, except that the metal lithium negative electrode D1 prepared in Comparative Example 1 was used as the negative electrode. The cycle results are shown in Figure 2 As shown in the figure:

[0157] The metal lithium negative electrode D1 prepared in Comparative Example 1 has a 2 @1mAh / cm 2 The cycle life under these conditions is only 175h.

[0158] It can be seen from the above results that the metal lithium negative electrode prepared by using the metal lithium negative electrode current collector provided by the present invention has better cycle performance.

[0159] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A metallic lithium negative electrode current collector, characterized in that: The current collector comprises a substrate and a protective layer, wherein the substrate is a carbon nano cage having a hollow cavity and a graphitized carbon layer shell; the protective layer conformally covers the outer surface and the inner surface of the graphitized carbon layer shell; the protective layer contains a lithium-containing compound, wherein the lithium-containing compound is selected from at least one of LiF, Li2CO3, LiOH, Li3PO4, LiPF6, LiTFSI, LiFSI, Li2SO3, LiNO3, Li2O, Li3N and R1-COOLi, wherein R1 is C1-C 20 alkyl.

2. The metal lithium negative electrode current collector according to claim 1, wherein: The diameter of the matrix is ​​2-200 nm; and / or, the volume of the hollow chamber accounts for 50-98% of the total volume of the carbon nanocage; And / or, the thickness of the graphitized carbon layer shell is 1-50 nm.

3. The metal lithium negative electrode current collector according to claim 2, wherein: The diameter of the matrix is ​​10-50 nm; and / or, the volume of the hollow chamber accounts for 60-98% of the total volume of the carbon nanocage; And / or, the thickness of the graphitized carbon layer shell is 1-10 nm.

4. The metal lithium negative electrode current collector according to claim 3, wherein: The diameter of the matrix is ​​20-50 nm; And / or, the thickness of the graphitized carbon layer shell is 1-5 nm.

5. The metal lithium negative electrode current collector according to claim 1, wherein: The specific surface area of ​​the substrate is 50-1000m 2 / g; and / or, the pore volume of the matrix is ​​1-2 cm³ / g; and / or, the pore size distribution curve of the substrate has at least one mesopore distribution peak; And / or, in the Raman spectrum of the matrix, I D / I G The range is 0.2-1.

2.

6. The metal lithium negative electrode current collector according to claim 5, wherein: The specific surface area of ​​the substrate is 200-600m 2 / g; and / or, the pore volume of the matrix is ​​1.5-1.8 cm³ / g; And / or, the pore size distribution curve of the matrix has two mesopore distribution peaks; And / or, in the Raman spectrum of the matrix, I D / I G The range is 0.2-0.

5.

7. The metal lithium negative electrode current collector according to claim 6, wherein: In the pore size distribution curve of the matrix, there is a first mesopore distribution peak at 2-10 nm, and a second mesopore distribution peak at 15-30 nm.

8. The metal lithium negative electrode current collector according to claim 1, wherein: The lithium-containing compound is selected from at least one of LiF, Li2CO3, LiOH, Li2O and Li3N; and / or Based on the total weight of the protective layer, the content of the lithium compound in the protective layer is 100% by weight; And / or, based on the total weight of the current collector, the content of the protective layer is 1-20 wt %.

9. The metal lithium negative electrode current collector according to claim 8, wherein: Based on the total weight of the current collector, the content of the protective layer is 1-5% by weight.

10. A method for preparing the metal lithium negative electrode current collector according to any one of claims 1 to 9, characterized in that: The method comprises: The substrate is contacted and reacted with the pretreatment liquid by vacuum infiltration; the substrate is a carbon nanocage with a hollow cavity and a graphitized carbon layer shell; the pretreatment liquid contains a lithium salt, and the lithium salt is selected from at least one of LiPF6, LiTFSI, LiFSI and LiNO3.

11. The method according to claim 10, wherein: Contacting the substrate with the pretreatment solution at a temperature below 10 Pa; and / or The usage ratio of the substrate to the pretreatment liquid is 0.1-0.3 g: 15-25 mL; and / or The pretreatment solution further contains a solvent; and / or, the pretreatment solution is obtained by mixing a lithium salt with a solvent; and / or, in the pretreatment solution, the concentration of lithium salt is 0.1-0.5 g / mL; And / or, contacting the substrate with the pretreatment liquid for reaction comprises: dropping the pretreatment liquid onto the surface of the substrate and stirring; And / or, the contact reaction conditions include: temperature of 20-50° C.; time of 1-10 h.

12. The method according to claim 11, wherein: The usage ratio of the substrate to the pretreatment liquid is 0.15-0.25 g: 20-23 mL; and / or, the solvent is an organic solvent; and / or, in the pretreatment solution, the concentration of lithium salt is 0.15-0.3 g / mL; And / or, the contact reaction conditions include: a temperature of 20-30°C; The time is 2-4h.

13. The method according to claim 12, wherein: The solvent is selected from at least one of ethylene carbonate, dimethyl carbonate, 1,3-dioxolane and ethylene glycol dimethyl ether.

14. The method according to claim 10, wherein: The method for preparing the substrate comprises the following steps: (1) providing a homogeneous solution containing a nickel source, an organic carboxylic acid and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; (2) calcining the precursor at a high temperature under an inert atmosphere or a reducing atmosphere to obtain a calcined product; (3) contacting the calcined product with an acid for reaction, and then performing solid-liquid separation to obtain a matrix.

15. The method according to claim 14, wherein: In step (1), the mass ratio of the nickel source to the organic carboxylic acid is 1:0.1-100; And / or, the nickel source is selected from at least one of nickel acetate, nickel chloride, nickel carbonate and basic nickel carbonate; and / or The organic carboxylic acid is selected from at least one of citric acid, maleic acid, trimesic acid, terephthalic acid, malic acid, ethylenediaminetetraacetic acid and dipicolinic acid; and / or The solvent is water and / or ethanol.

16. The method according to claim 15, wherein: In step (1), the mass ratio of the nickel source to the organic carboxylic acid is 1:0.2-50; And / or, the nickel source is basic nickel carbonate; And / or, the organic carboxylic acid is citric acid; And / or, the solvent is water.

17. The method according to claim 16, wherein: In step (1), the mass ratio of the nickel source to the organic carboxylic acid is 1:0.5-5.

18. The method according to claim 14, wherein: In step (2), the high temperature calcination conditions include: a heating rate of 0.5-30°C / min; a temperature of 600-1300°C; and a calcination time of 20-600 min. and / or, the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium; And / or, the reducing atmosphere is provided by hydrogen and optionally an inert gas.

19. The method according to claim 18, wherein: In step (2), the high temperature calcination conditions include: a heating rate of 1-10°C / min; a temperature of 800-1100°C; and a time of 60-480 min.

20. The method according to claim 14, wherein: In step (3), the contact reaction conditions include: temperature of 20-110° C.; time of 0.1-48 h; and / or the acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid.

21. The method according to claim 20, wherein: In step (3), the contact reaction conditions include: temperature of 60-90°C; time of 4-12h; And / or, the acid is hydrochloric acid.

22. A metal lithium negative electrode, comprising a metal foil and an active layer composited on the metal foil, characterized in that: The active layer comprises a binder, an optional conductive agent, a current collector and metallic lithium filled in the current collector, and the current collector is the metallic lithium negative electrode current collector according to any one of claims 1 to 9.

23. The metallic lithium negative electrode according to claim 22, wherein: The metallic lithium is filled in the hollow cavity of the metallic lithium negative electrode current collector; and / or the metallic lithium passes through the graphitized carbon layer shell and / or the protective layer of the metallic lithium negative electrode current collector and is filled in the hollow cavity; and / or Based on the total weight of the active layer, the content of metallic lithium is 2-90% by weight; and / or Based on the total weight of the active layer, the content of the metal lithium negative electrode current collector is 20-50% by weight; and / or, the content of the binder is 5-20% by weight; and / or, the content of the conductive agent is 0-10% by weight; And / or, the thickness of the active layer is 5-50 μm; And / or, the metal foil is selected from at least one of copper foil, titanium foil, nickel foil and alloy foils thereof; and / or, the metal foil has a thickness of 5-20 μm.

24. The metallic lithium negative electrode according to claim 23, wherein: Based on the total weight of the active layer, the content of metallic lithium is 10-50% by weight; and / or, based on the total weight of the active layer, the content of the metal lithium negative electrode current collector is 25-40% by weight; and / or, the content of the binder is 10-20% by weight; and / or, the content of the conductive agent is 5-10% by weight; And / or, the thickness of the active layer is 10-50 μm; And / or, the metal foil is copper foil; and / or, the thickness of the metal foil is 8-10 μm.

25. A method for preparing a metallic lithium negative electrode, characterized in that: The method comprises: The slurry containing the current collector, the binder, and the optional conductive agent and solvent is coated on the metal foil, dried, rolled or not rolled, and then subjected to an electrodeposition reaction with metallic lithium; The current collector is the metal lithium negative electrode current collector according to any one of claims 1 to 9.

26. The method according to claim 25, wherein: The electrodeposition is constant direct current electrodeposition and / or pulse electrodeposition; and / or The binder is selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber emulsion and acrylonitrile copolymer aqueous dispersion; and / or, the conductive agent is selected from at least one of conductive carbon black, acetylene black, nickel powder, copper powder and conductive graphite; and / or The solvent is anhydrous ethanol and / or N-methylpyrrolidone; And / or, the mass ratio of the current collector, the binder and the conductive agent is 50-90:5-20:0-10.

27. The method according to claim 26, wherein: The electrodeposition is a constant direct current electrodeposition; And / or, the binder is polyvinylidene fluoride; And / or, the conductive agent is conductive carbon black; And / or, the solvent is N-methylpyrrolidone; And / or, the mass ratio of the current collector, the binder and the conductive agent is 60-80:10-20:5-10.

28. A metal lithium battery, comprising a pole core and a non-aqueous electrolyte, wherein the pole core and the non-aqueous electrolyte are sealed in a battery housing, the pole core comprises a positive electrode, a negative electrode and a diaphragm, the diaphragm is located between the positive electrode and the negative electrode, characterized in that: The negative electrode is the metal lithium negative electrode as described in any one of claims 22-24 or is the metal lithium negative electrode prepared according to the method as described in any one of claims 25-27.

29. The metal lithium battery according to claim 28, wherein: The metal lithium battery is any one of a lithium oxygen battery, a lithium sulfur battery, a lithium selenium battery, a lithium tellurium battery, a lithium iodine battery, a lithium carbon dioxide battery and a lithium nitrogen battery.

Citation Information

Patent Citations

  • Metal lithium negative electrode for secondary battery and preparation and application thereof

    CN110783529A

  • Metal lithium@carbon composite material, lithium metal anode, and preparation and application of metal lithium@carbon composite material

    CN110875471A